2013
DOI: 10.1103/physreve.88.052811
|View full text |Cite
|
Sign up to set email alerts
|

Percolation in multiplex networks with overlap

Abstract: From transportation networks to complex infrastructures, and to social and communication networks, a large variety of systems can be described in terms of multiplexes formed by a set of nodes interacting through different networks (layers). Multiplexes may display an increased fragility with respect to the single layers that constitute them. However, so far the overlap of the links in different layers has been mostly neglected, despite the fact that it is an ubiquitous phenomenon in most multiplexes. Here, we … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
195
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 191 publications
(201 citation statements)
references
References 42 publications
4
195
2
Order By: Relevance
“…Therefore, it is of crucial importance to determine the robustness of multiplex networks in the presence of this structural feature. In order to model multiplex networks with link overlap, the notion of multilinks [9,37,42] turns out to be extremely useful. Two nodes i and j are connected by a multilink m = (m 1 ,m 2 , .…”
Section: Multiplex Network With Link Overlapmentioning
confidence: 99%
See 2 more Smart Citations
“…Therefore, it is of crucial importance to determine the robustness of multiplex networks in the presence of this structural feature. In order to model multiplex networks with link overlap, the notion of multilinks [9,37,42] turns out to be extremely useful. Two nodes i and j are connected by a multilink m = (m 1 ,m 2 , .…”
Section: Multiplex Network With Link Overlapmentioning
confidence: 99%
“…V we present the multilink definitions in the case of link overlap, using the formalism of Ref. [42]. In Sec.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, in biological systems basic constituents such as proteins can have physical, co-localization, genetic or many other types of interactions. Recently, it has been shown that retaining such multi-dimensional information 7 and modelling the structure of interdependent and multilayer systems respectively through interdependent 8 and multilayer networks [9][10][11][12] reveals new nontrivial structural properties [13][14][15][16][17][18][19][20] and relevant emergent physical phenomena [21][22][23][24][25][26][27] .…”
mentioning
confidence: 99%
“…Recent studies alone this line include empirical analysis of real-world network data [11,12], evolution of network structures [13][14][15], and new critical phenomena and processes occurring on them [9,10,16,17]. These coupled networks exhibit some common features, such as the inter degree-degree correlation [18], inter-similarity [19], multiple dependence in providing support [9], and node and edge overlapping between layers [20]. These features have important effects on critical phenomena and the dynamics, including percolation [9], cascading failure [16], diffusion processes [21], emergence of cooperation [22] and epidemic dynamics [17], when compared with those in a single network.…”
Section: Introductionmentioning
confidence: 99%